Comparative political economy of the IMF arrangements after the Arab uprisings: Egypt and Tunisia. Issue 5 (19th October 2016) - Hecan, Mehmet
ABSTRACT: In the post-uprising period, while Tunisia was relatively successful in its negotiations with the International Monetary Fund (IMF), which provided it with a stand-by agreement in the amount of 1.74 billion, Egypt remained far from reaching any agreement. In an attempt to explain the difference between the IMF experiments in the two countries, that is, the factors leading to the signing of an agreement with the IMF or the inability to do so, this article proposes two arguments, based upon one positive and one negative factor: (1) distinctive domestic political dynamics and (2) the availability of alternative resources. In the two cases, the article argues that the IMF experiment was more successful in Tunisia because Tunisia enjoyed a more suitable domestic political environment which promoted and enabled reforms and thus enabled the negotiations with the IMF. Tunisia also lacked alternative resources that could be used as substitutes for the IMF loan. On the other hand, the IMF negotiations were not successful in Egypt as mounting social and political opposition decreased the ability of the government to maintain economic reforms and negotiate an IMF loan and the existence of alternative resources created disincentives. Furthermore, not only pointing out the importance of 'alternative funds' and the 'domestic political environment' with regard to the demand side of the IMF loans, this article also debates the relative strengths of the variables, and argues that alternative funds matter more than the domestic political environment.